2016
DOI: 10.3390/w8100473
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Water Footprints of Vegetable Crops: Influence of Growing Season, Solar Radiation Data and Functional Unit

Abstract: Abstract:Water footprint (WF) accounting as proposed by the Water Footprint Network (WFN) can potentially provide important information for water resource management, especially in water scarce countries relying on irrigation to help meet their food requirements. However, calculating accurate WFs of short-season vegetable crops such as carrots, cabbage, beetroot, broccoli and lettuce presented some challenges. Planting dates and inter-annual weather conditions impact WF results. Joining weather datasets of jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 41 publications
0
16
1
2
Order By: Relevance
“…In addition, we converted the water footprint values of selected alien vegetables to water productivity values (Table 2A.2); at a glance, these values are higher compared to the values of this study. Probably the water footprint values from Le Roux et al (2016) and Mekonnen and Hoekstra (2011) were calculated on a fresh mass basis. Therefore, alien vegetables might have high water footprint if a fresh mass was used, but if a dry mass was used, water footprints of these vegetables could be relatively low (Le Roux et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we converted the water footprint values of selected alien vegetables to water productivity values (Table 2A.2); at a glance, these values are higher compared to the values of this study. Probably the water footprint values from Le Roux et al (2016) and Mekonnen and Hoekstra (2011) were calculated on a fresh mass basis. Therefore, alien vegetables might have high water footprint if a fresh mass was used, but if a dry mass was used, water footprints of these vegetables could be relatively low (Le Roux et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Probably the water footprint values from Le Roux et al (2016) and Mekonnen and Hoekstra (2011) were calculated on a fresh mass basis. Therefore, alien vegetables might have high water footprint if a fresh mass was used, but if a dry mass was used, water footprints of these vegetables could be relatively low (Le Roux et al, 2016). Le Roux et al (2016) found that the water footprints of maize and wheat were higher than those of vegetables if expressed in terms of fresh mass; however, when expressed in terms of dry mass, the water footprints of maize and wheat were similar to those of vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen of the fourteen papers in this special issue consider green and blue WFs [14][15][16][17][18][19][20][21][22][23][24][25][26], while eight papers include grey WF estimation. All papers that include the grey WF specifically focus on pollution through nitrogen [14,15,17,19,21,22,25,27].…”
Section: The Papers In This Special Issue: Measuring Efficiency and Smentioning
confidence: 99%
“…All papers that include the grey WF specifically focus on pollution through nitrogen [14,15,17,19,21,22,25,27]. The only paper that exclusively focuses on the grey WF is the one by Brueck and Lammel [27].…”
Section: The Papers In This Special Issue: Measuring Efficiency and Smentioning
confidence: 99%
See 1 more Smart Citation